2017
DOI: 10.18632/oncotarget.16750
|View full text |Cite
|
Sign up to set email alerts
|

Expression of embryonal stem cell transcription factors in breast cancer: Oct4 as an indicator for poor clinical outcome and tamoxifen resistance

Abstract: The transcription factors of embryonic stem cells, such as Oct4, Sox2, Nanog, Bmi1, and Klf4, are known to be associated with stemness, epithelial–mesenchymal transition and aggressive tumor behavior. This study was designed to evaluate the clinicopathological significance of their expression in breast cancer. Immunohistochemistry for Oct4, Sox2, Nanog, Bmi1, and Klf4 was performed in 319 cases of invasive breast cancer. The relationship between the expression of these markers and clinicopathologic features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 37 publications
13
63
0
1
Order By: Relevance
“…78 Data also show that Oct4 expression is associated with poor clinical outcome in hormone receptor-positive breast cancer. 79 Knockdown of Oct4 also reduces the stemness of germ cell tumors. 80 Hence, these studies have proven that Oct4 is a pluripotent factor in CSCs.…”
Section: Major Transcription Factors In Cscsmentioning
confidence: 99%
“…78 Data also show that Oct4 expression is associated with poor clinical outcome in hormone receptor-positive breast cancer. 79 Knockdown of Oct4 also reduces the stemness of germ cell tumors. 80 Hence, these studies have proven that Oct4 is a pluripotent factor in CSCs.…”
Section: Major Transcription Factors In Cscsmentioning
confidence: 99%
“…Increased stability of the KLF4 protein, which is mediated by the ubiquitin-proteasomal pathway, is linked to an oncogenic role in breast cancer (Hu et al 2012), and decreased stability is linked to its tumor suppressor role in colorectal cancer (Gamper et al 2012). KLF4 stability modulation by interaction with the pluripotency transcription factors may also be important in tumorigenesis, as coexpression of these factors is associated with a variety of cancers such as breast cancer, squamous cell carcinoma, and gastrointestinal cancer progression (Hu et al 2012;Lu et al 2014;Piva et al 2014;Almozyan et al 2017;Gwak et al 2017;Soheili et al 2017).…”
Section: Klf4 Protein Stability Is Modulated In Es Cellsmentioning
confidence: 99%
“…Tumor cells with a more aggressive phenotype display strong self‐renewal capacity and tumorigenicity under average chemotherapy pressure, which are similar characteristics to those harboured by CSCs that enable them to escape drug‐induced cell death . For example, Oct4 overexpression contributes to tamoxifen resistance and ALDH1 upregulation in hormone receptor‐positive breast cancer . Silencing SOX2 expression also attenuates the resistance to cisplatin in glioblastoma multiforme .…”
Section: Disscussionmentioning
confidence: 99%
“…39,40 For example, Oct4 overexpression contributes to tamoxifen resistance and ALDH1 upregulation in hormone receptor-positive breast cancer. 41 Silencing SOX2 expression also attenuates the resistance to cisplatin in glioblastoma multiforme. 42 Our study demonstrated that chemoresistant TSCC cells acquired abilities similar to CSCs, which were accompanied by an increase in the CSC markers ABCG2, SOX2, OCT4, and BMI1 as well as strong self-renewal capacity and tumorigenicity in vivo.…”
Section: Disscussionmentioning
confidence: 99%